2004
DOI: 10.1387/ijdb.041862ns
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new modes of Dd-STATa regulation of gene expression in Dictyostelium by in situ hybridisation

Abstract: We identified 13 genes which are candidates for direct induction by Dd-STATa. In the parental strain, most of these genes are expressed in the cone shaped mass of pstAB cells which is located within the prestalk region. These cDNAs show little or no expression in the Dd-STATa-null strain. This contrasts markedly with the paradigmatic ecmB gene which is expressed in pstAB cells in parental cells, but which is expressed throughout the prestalk zone in the Dd-STATa-null strain. We also identified several genes wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 16 publications
2
41
0
Order By: Relevance
“…Reduced SSK395 gene expression in Dd-STATa-null mutant at the late slug stage but not at the early stages Interestingly, although expression at the tipped finger stage is detectable in the Dd-STATa null mutant, the transcript is hardly detectable in the mutant at the late slug stage (Shimada et al, 2004a). Therefore, only later expression appears to be positively regulated by Dd-STATa.…”
Section: Prestalk Cell-specific Expression Of the Ssk395 Genementioning
confidence: 89%
See 4 more Smart Citations
“…Reduced SSK395 gene expression in Dd-STATa-null mutant at the late slug stage but not at the early stages Interestingly, although expression at the tipped finger stage is detectable in the Dd-STATa null mutant, the transcript is hardly detectable in the mutant at the late slug stage (Shimada et al, 2004a). Therefore, only later expression appears to be positively regulated by Dd-STATa.…”
Section: Prestalk Cell-specific Expression Of the Ssk395 Genementioning
confidence: 89%
“…In a previous study, we identified 13 prestalk-specific genes whose expression is down regulated in the Dd-STATa-null mutant (Shimada et al, 2004a). One of those is an EST clone SSK395, which is detectable at the tipped finger stage by in situ hybridization (Shimada et al,2004a).…”
Section: Prestalk Cell-specific Expression Of the Ssk395 Genementioning
confidence: 99%
See 3 more Smart Citations